BisGMA/jute fiber/fly ash hybrid composites. Issue 5 (19th August 2014) - Praharaj, Ankita Pritam; Behera, Dibakar; Bastia, Tapan Kumar; Rath, Prasanta; Mohanty, Priyabrata
Abstract : Purpose: This paper seeks to prepare BisGMA/Jute fiber/Fly Ash hybrid composites with improved mechanical and corrosive properties. Design/methodology/approach: BisGMA (bisphenol-A glycidyldimethacrylate) prepolymer was first synthesised using diglycidyl ether of bisphenol-A (DGEBA) and methacrylic acid. Then 2-hydroxy ethylacrylate (HEA) treated jute fiber and sodium hydroxide (NaOH) treated fly ash were incorporated in the fabrication of composites using Dicumyl Peroxide (DCP), Cobalt naphthenate and N, N-dimethyl aniline (DMA) as catalyst, accelerator and promoter respectively. The composition of BisGMA, jute fiber and fly ash were kept constant whereas treated and untreated jute fiber and fly ash were used alternatively. Findings: Treatment of both jute and fly ash leads to improved mechanical properties of composites. However, treated fabric plays a dominant role compared to treated fly ash as filler. Amongst all the composites, the one having both treated jute fiber and treated fly ash is the most suitable composite for structural applications. Research limitations/implications: The present investigation has come up with a hybrid composite that can be used for a wide range of applications like low cost housing and structural projects, structural laminates etc since it is both corrosion and moisture resistant. It is also the most durable from the mechanical point of view. There is also a scope of using other fillers instead of fly ash in order to study the changes brought about in the mechanical properties. Originality/value: The above composites have never been fabricated before.